Assessment of Knowledge, Awareness and Practices among Healthcare Professionals about Pharmacovigilance and Adverse Drug Reactions Reporting in Dharmapuri and Krishnagiri Districts of Tamilnadu, India - Damodar, Shyam Kumar; Joseph, Jitto; Cheaten, Suhas; Rajendran, Nanjappan; Vijayan, Pranav M; Guru, G (Journal of Pharmacy Practice and Community Medicine)
Background: Adverse drug reactions are scantly reported by healthcare professionals worldwide and in particular in developing countries. Therefore the aim of the current study was to assess the knowledge, awareness and practices of health care professionals about pharmacovigilance and adverse drug reaction reporting of Dharmapuri and Krishnagiri districts in Tamil Nadu. Methods: A cross-sectional study using a validated questionnaire was designed to address theawareness of ADRs, knowledge of Pharmacovigilance system and practices of Pharmacovigilance system. The questionnaire was distributed to randomly selected healthcare professionals (n= 350) such as doctors, pharmacists, nurses and pharmacists’ technicians of hospitals. Completed questionnaires were collected and data were analyzed. Data were expressed in number as well as percentage. Results: Of the 350 questionnaires circulated, a total of 264 healthcare professionals responded. HealthCare professional categories involved in the study were these 86 were doctors, 91 were nurses and 87 were pharmacists. These 86 were doctors, 91 were nurses and 87 were pharmacists. And the overall percent of the respondents who accepted to enroll in the study was about 75.4%. Conclusion: In the present study, we observed that healthcare professionals have little knowledge about the concept and the process of Pharmacovigilance and spontaneous ADRs reporting system. However, they had positive approach towards Pharmacovigilance but very little experience with reporting. Our study has demonstrated a lack of knowledge and awareness of Pharmacovigilance and ADRs reporting among healthcare professionals in hospitals and also there is a need of a nearby ADR monitoring centre in Dharmapuri and Krishnagiri area
Keywords: Pharmacovigilance; Adverse drug reactions (ADR); Questionnaire; Awareness and practices; Health care professionals